2021
DOI: 10.1186/s42774-021-00094-7
|View full text |Cite
|
Sign up to set email alerts
|

Transfer learning for deep neural network-based partial differential equations solving

Abstract: Deep neural networks (DNNs) have recently shown great potential in solving partial differential equations (PDEs). The success of neural network-based surrogate models is attributed to their ability to learn a rich set of solution-related features. However, learning DNNs usually involves tedious training iterations to converge and requires a very large number of training data, which hinders the application of these models to complex physical contexts. To address this problem, we propose to apply the transfer le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The reduction in the amount of training time is substantial, especially when the Reynolds numbers in the targeted DNN and base DNN are close. This observation is consistent with the finding reported by Chen et al [36].…”
Section: Transfer Learningsupporting
confidence: 94%
See 1 more Smart Citation
“…The reduction in the amount of training time is substantial, especially when the Reynolds numbers in the targeted DNN and base DNN are close. This observation is consistent with the finding reported by Chen et al [36].…”
Section: Transfer Learningsupporting
confidence: 94%
“…This technique has been successfully applied to the fields of computer vision and natural language processing. In one recent work by Chen et al [36], it was shown that for solving N-S equations at different Reynolds numbers using PINN, the re-training benefited from the transfer learning technique.…”
Section: Transfer Learningmentioning
confidence: 99%
“…Transfer learning. One limitation of the network-based method to solve PDEs is the slow training speed, and there is some work to improve this, such as the transfer learning [8] and manifold learning [24]. For the Boltzmann equation, especially for the BGK model, the classical methods such as 3) The relative error between the numerical solution by NR/NSR and the reference solution for the density ρ, macroscopic velocity u 1 and the temperature T with Kn = 0.01, 0.1 and 1 at t = 0 and 0.1.…”
Section: Algorithm 51 Obtain the Data-driven Collision Kernelmentioning
confidence: 99%
“…In addition, the grid search algorithm and early stopping are utilized to find architectures that achieve satisfying performance on specific physical problems within a short time period. By using this framework, accurate prediction results can be obtained, and at the same time transfer learning [28], [30] is utilized to increase the scalability of the trained model. By utilizing the similarities between equations, it can greatly improve the training efficiency for solving different problems.…”
Section: Introductionmentioning
confidence: 99%